2006
DOI: 10.1088/0953-4075/39/20/009
|View full text |Cite
|
Sign up to set email alerts
|

Atomic hydrogen revisited: electron impact excitation to H(2p) at 54 eV

Abstract: New measurements of the three reduced Stokes parameters for 54.4 eV electron impact excitation of the 2p state of atomic hydrogen support convergent close coupling and propagating exterior complex scaling theoretical values within two standard deviations and over a larger angular range of 2°–140° than earlier work. Whereas the present measurements and theoretical values of the circular polarization Stokes parameter P3 agree, they differ by up to about four standard deviations from the measurements by Gradziel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…PECS reduced Stokes parametersP 1 ,P 2 andP 3 and related parameters P l , γ and P + for e-H 1s-2p scattering at E 0 = 54.4 eV. CCC box-based calculations (CCC-B) [40] and measurements of Yalim et al [65], Gradziel and O'Neill [64] and Williams and Mikosza [66] are also shown.…”
Section: Ground-state Hydrogen Scatteringmentioning
confidence: 77%
“…PECS reduced Stokes parametersP 1 ,P 2 andP 3 and related parameters P l , γ and P + for e-H 1s-2p scattering at E 0 = 54.4 eV. CCC box-based calculations (CCC-B) [40] and measurements of Yalim et al [65], Gradziel and O'Neill [64] and Williams and Mikosza [66] are also shown.…”
Section: Ground-state Hydrogen Scatteringmentioning
confidence: 77%
“…Figure 8.19 shows the angle-integrated cross section for elastic scattering and electron-impact excitation from the (1s) 2 S state of atomic hydrogen. The excellent agreement between predictions from the CCC, RMPS, and IERM methods, as well as with the experimental data of Williams (1988), indicates that these sophisticated methods can indeed solve this problem to a very high degree of accuracy. Stepanovic et al (2006) recently measured the angle-integrated cross sections for electron-impact excitation of the 3 3 S and 3 1 S states of helium shown in figure 8.20.…”
Section: Inclusion Of Relativistic Effectsmentioning
confidence: 64%
“…The reduced Stokes parameters, P 1 , P 2 and P 3 for the H(2p) state at an incident electron energy of 54 eV. Closed squares, Yalim, Cvejanovic and Crowe (1997); closed and open circles, Williams and Mikosza (2006); closed triangles, Gradziel and O'Neill (2004); open triangles, O'Neill et al (1998);open squares, Nic Chormaic, Chwirot and Slevin (1993); open diamonds, Williams (1986); full line, the PECS theory of Bartlett et al (2005). Adapted from Williams and Mikosza (2006 More detailed reviews of angular and polarization correlation and superelastic scattering studies were given by Andersen, Gallagher and Hertel (1988) Andersen et al (1997), and Andersen and Bartschat (2001).…”
Section: Angular and Polarization Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron-photon coincidence technique has been used to study collisions with different atomic targets, both experimentally and theoretically. These include the lighter targets hydrogen [4][5][6], helium [7,8], and magnesium [9,10]; intermediate targets including calcium [11][12][13][14][15][16], neon [17][18][19], and zinc [20][21][22][23]; and heavier targets including cadmium [24][25][26], lead [27], and mercury [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%